Characteristics of Ti(C, N)/TiB composite layer on Ti–6Al–4V alloy produced by laser surface melting. (June 2016) - Zeng, Xian; Yamaguchi, Tomiko; Nishio, Kazumasa
Abstract: A Ti(C, N)/TiB reinforced titanium matrix composite layer was successfully in-situ synthesized by laser melting on Ti–6Al–4V alloy surface with Ti–BN–C mixed powder, aiming at improving the wear resistance. The microstructure, chemical composition, hardness and wear behavior were analyzed. The results showed that, the cross sectional microstructure can be clearly divided into three parts, which were the laser melted layer, heat affected zone and non-affected zone. The reinforcements in laser melted layer consisted of dendritic TiC0.3 N0.7 phases and fine-structure TiB phases. The matrix in laser melted layer was in a two-phase structure, being composed of platelet α titanium and intergranular β titanium. The hardness was increased from 320 HV in the substrate to 450–550 HV in the modified layer. The wear resistance was improved that, the wear volume loss of the laser treated sample was approximately half of the as received Ti–6Al–4V alloy after 8 h wear test. Highlights: The formation of Ti(C, N)/TiB layer by laser melting was initially studied. The microstructures were analyzed using XRD, SEM, EPMA and TEM methods. The hardness was improved by 250–300 HV as compared with substrate. The wear volume loss was reduced by half of the untreated substrate.